The age of insight : the quest to understand the unconscious in art, mind, and brain : from Vienna 1900 to the present - Kandel, Eric R. (Random House, 2011)
"The Age of Insight" takes readers to Vienna in 1900, where leaders in science, medicine, and art began a revolution that changed forever how we think about the human mind--our conscious and unconscious thoughts and emotions--and how mind and brain relate to art.